Microparasites in selected populations of wild Atlantic salmon (Salmo salar) in Norway – Prevalence, density and diversity - Kambestad, Martha Amalie (The University of Bergen, 2019)
The aim of this study was to investigate the prevalence, density and diversity of microparasites in Atlantic salmon from selected populations in Norway including and to provide an assessment of the possible spreading of microparasites between farmed- and wild salmonids. This was done by real time RT PCR screening of RNA extracted from gill tissues. The main focuses has been on SAV2 which has recently been introduced to Norway and is causing frequent outbreaks of PD in Trøndelag. The introduction of this virus makes it possible to investigate the potential transmission between wild and farmed salmon. There is reason to believe that SAV has been spread over longer distances by transport of smolt and between fish farms by currents. The high density of infected populations might cause a high infection pressure on wild salmon migrating in these areas. An increased understanding of a potential impact from the aquaculture industry on wild salmon populations can be acquired by investigating the presence of selected microparasites in wild salmon populations in areas with aquaculture. This to see if there is a connection between outbreaks of pathogenic disease and the occurrence of the causative agent in the wild populations, or if the wild salmon represents a natural reservoir. Collection of salmon from both sea and rivers enables the possible detection of difference in prevalence and the effect of these microparasites on wild populations. SAV was not detected in any of the wild salmonids from Trøndelag and Finnmark during this study, however four Atlantic salmon from Hordaland were positive for the presence of SAV, one of them an escaped farmed salmon. Other viruses such as ISAV, SGPV and PRV that are quite prevalent in farmed salmon have also been detected with relatively high prevalences in wild salmon populations. There was a higher prevalence of both ISAV- and PRV-positive salmon were found in the sea compared to rivers indicating that transmission of these viruses happens when the salmon are migrating in the sea. ...